A holding control strategy for diverging bus lines. (May 2021) - Laskaris, Georgios; Cats, Oded; Jenelius, Erik; Rinaldi, Marco; Viti, Francesco
Highlights: The holding criterion accounts for all passengers groups. The holding criterion manages to maintain all travel time components low. Performance loss is observed when lines transition from common to individual segments. Multi-line control is recommended for the majority of demand segmentations scenarios. Abstract: Holding has been extensively used as control strategy to regulate public transport operations, especially to maintain even headways and prevent buses of the same line to bunch up. Applying holding to multiple lines requires however to deal with the transition between corridor and branching segments. In this study, we introduce a holding criterion for network configurations with lines that operate jointly along a common corridor and then diverge to individual branches serving different urban areas. The proposed holding decision rule accounts for all different passenger groups in the overlapping segment and considers the transition to individual line operation. The holding rule is evaluated using simulation for different demand levels and compositions and is compared with state-of-the-art control schemes for a real-world network. Results show that the proposed multi-line control yields performance improvements along the shared transit corridor as well as at the line level. The performance of the control scheme is affected by the demand composition and we provide indications regarding the conditions under which multi-line control is advisable.